Chiral-at-Ru Catalyst with Cyclometalated Imidazo[1,5-a]pyridinylidene for Enantioselective Intramolecular Cyclopropanations - Han, Feng; Xie, Yuanhao; Xie, Xiulan; Ivlev, Sergei I.; Meggers, Eric (Synlett, 2022)
A chiral ruthenium catalyst is introduced which contains a cyclometalated N-(3-nitrophenyl)-imidazo[1,5-a]pyridinylidene ligand in addition to a bidentate 4-mesityl-2-(pyridin-2-yl)thiazole and two acetonitriles to complement the octahedral coordination sphere of the monocationic complex. Tetrafluoroborate serves as the counterion. Since all coordinated ligands are achiral, the overall chirality is formally due to a stereogenic metal center generating either a left-handed (Λ) or right-handed (Δ) helical topology of this chiral-at-metal complex. Nonracemic Λ and Δ complexes were synthesized using (R)- and (S)-N-benzoyl-tert-butanesulfinamide as chiral auxiliary ligands, respectively. The position of the nitro group in the metalated phenyl moiety is of crucial importance for the generation of enantiomerically pure complexes. The catalytic activity of the cycloruthenated chiral-at-metal catalyst was demonstrated for the enantioselective intramolecular cyclopropanation of trans-cinnamyl diazoacetate and an alkenyl diazoketone to generate bicyclic cyclopropanes in high yields (96–97%) and with satisfactory enantioselectivity (93% ee).
Keywords: cyclometalation; imidazo[1,5-a]pyridinylidene; chiral-at-metal; stereogenic metal; ruthenium; asymmetric catalysis; cyclopropanation